Mechanically interlocked and switchable molecules at surfaces. - Davis, J; Orlowski, G; Rahman, H; Beer, P (2010)
Mechanically interlocked molecules are of considerable interest from data storage, molecular scale or sensory device perspectives. Though the solution phase characterisation of these compounds has been extensively explored, progress towards real world application will, in many cases, necessitate a detailed understanding of their interfacing with supportive, optically transparent or electroactive surfaces. This feature article summarises the developments made in surface assembly and characterisation including recent progress in exploiting templating methods to interlock molecular systems on surfaces.